2010
DOI: 10.1016/j.medin.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la eosinopenia como marcador de infección en pacientes ingresados en una Unidad de Cuidados Intensivos

Abstract: In a medical-surgical ICU, the capacity to discriminate infection through examining eosinopenia is not high. It could be useful to rule out infection if we combined eosinopenia with monocytes count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Several studies [4][8] have suggested that eosinopenia can be a marker of bacterial infection in distinct types of patients. These studies include heterogeneous populations and have a small number of patients, representing a major limitation for their interpretation, which is reflected in their contradictory results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [4][8] have suggested that eosinopenia can be a marker of bacterial infection in distinct types of patients. These studies include heterogeneous populations and have a small number of patients, representing a major limitation for their interpretation, which is reflected in their contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…This author also suggested that an increase in eosinophils could indicate that recovery had begun. Several studies have used eosinophil counts, specifically eosinopenia, as a marker of infection [4][8] and as an indicator of bacteremia [9][11], although the results are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…While the most acceptable cutoff for the eosinophil count in adults as a predictor of mortality is 40-50 cells/µL (10, 11, 20), our study suggested a lower level of 15 cells/µL in pediatric patients. This lower value can potentially be explained by either the greater vulnerability of children during severe inflammation and stress or the greater proportion of children who were medical, rather than surgical, ICU patients (medical vs surgical patients: 144 [95%] vs 6 [5%]) (21). …”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, eosinopenia has aroused much attention in its diagnostic and prognostic values for bacterial infection and sepsis, with some studies showing promising results. [10-15, 17, 18, 24, 25] However, the results of currently available studies on the diagnostic performance of eosinopenia are quite different, which is manifested by a range of sensitivity from 23.2-92.5% and a range of speci city from 28.57-91% [9][10][11][12][13][14][15]. Therefore, we conducted a meta-analysis to integrate all results from different studies in order to get the pooled outcomes…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of eosinopenia in diagnosis of sepsis was rstly tested by Abidi et al, who showed that eosinopenia is good at discriminating between non-infection and infection, but is rather weak in differentiating sepsis from systemic in ammatory response syndrome (SIRS) [9]. Given that there is a signi cant correlation between sepsis and eosinopenia, several studies carried out in addressing the value of eosinopenia to diagnose sepsis recently [9][10][11][12][13][14][15] and to predict the prognosis of sepsis [16][17][18] with pretty much inconsistence. With emerging of new studies on eosinopenia as a marker of sepsis, we determine to perform the present meta-analysis to reevaluate whether eosinopenia is a good biomarker for diagnosis of sepsis.…”
Section: Introductionmentioning
confidence: 99%